2017
DOI: 10.1111/1758-2229.12600
|View full text |Cite
|
Sign up to set email alerts
|

Differential oxidative stress tolerance of Streptococcus mutans isolates affects competition in an ecological mixed‐species biofilm model

Abstract: Streptococcus mutans strongly influences the development of pathogenic biofilms associated with dental caries. Our understanding of S. mutans behaviour in biofilms is based on a few well-characterized laboratory strains; however, individual isolates vary widely in genome content and virulence-associated phenotypes, such as biofilm formation and environmental stress sensitivity. Using an ecological biofilm model, we assessed the impact of co-cultivation of several S. mutans isolates with Streptococcus oralis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…In a separate study that focused on the effects of arginine on the antagonistic interactions between oral commensals and S. mutans, it was shown that enormous diversity exists among commensal streptococci, both in their antagonistic capabilities and their susceptibility to S. mutans (48). Clearly, probing the basis for phenotypic variation among commensals and pathogens (49) remains an essential goal in efforts to improve caries risk assessment and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study that focused on the effects of arginine on the antagonistic interactions between oral commensals and S. mutans, it was shown that enormous diversity exists among commensal streptococci, both in their antagonistic capabilities and their susceptibility to S. mutans (48). Clearly, probing the basis for phenotypic variation among commensals and pathogens (49) remains an essential goal in efforts to improve caries risk assessment and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences were observed, and were not only dependent on the sugars, but also on specific isolates. Liu S.S. et al (2017) revealed S. mutans isolates varied in their ability to compete and become dominant in the biofilm after the addition of sucrose ( Liu Y. et al, 2017 ). Interactions between microorganisms colonizing the oral cavity are consecutive factors affecting the development of biofilm, with interactions occurring between microorganisms resulting in both the acceleration and inhibition of this process ( Wen et al, 2010 ; Redanz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These species are considered commensal early colonizers [20,21,22]. All four species are beneficial to the host oral cavity in the context of their interactions with pathogenic species related both to caries and periodontal disease [23,24,25,26,27,28]. By extension, since oral health and overall general health are directly correlated, any disruption to the bacterial flora within the oral cavity could lead to systemic diseases, especially certain types of cardiovascular disease [29].…”
Section: Introductionmentioning
confidence: 99%